Economic Effects of Tariff Liberalization of Prospective India-GCC FTA: A Computable General Equilibrium Analysis. Issue 3 (August 2019) - Ismail, Saba; Ahmed, Shahid
The trade relations between India and the Gulf Cooperation Council (GCC) countries have been intensified during the last two decades. The GCC has emerged as one of the largest trading partner of India. This article attempts to investigate the result of tariff liberalization on welfare, output, employment and the potential trade flows between India and the GCC region using the GTAP-model. The study reveals that tariff liberalization has positive effects on India and GCC countries, with no or nominal negative effect on the rest of the world. Overall results show that India's trade relation with GCC countries is increasing continuously, but still there is a lot of untapped potential to bring the welfare gains for both trading partners. Finally, the study concludes that the proposed economic integration in terms of FTA between India and GCC will be mutually beneficial and welfare enhancing, and a case of a win–win situation. JEL Codes: F1, F13, F14, F17